Enhancing Fe tolerance in Al–Cu alloys by controlling the microstructure and mechanical properties with Mn and Cr additions - Jihao Li; Zhilei Xiang; Zian Yang; Wenchao Sun; Yang Han; Jingcun Huang; Xinshuo Gu; Xiaozhao Ma; Ziyong Chen (Journal of Materials Research and Technology)
Enhancing Fe-tolerance is beneficial to reduce reliance on high-purity electrolytic aluminum and lower resource consumption.This study focused on the influence of the combined addition of Mn and Cr on Fe-rich phase formation and dispersoid precipitation in Al-5.3 wt%Cu-0.18 wt%Fe cast alloys, as well as the relationship between microstructure and mechanical properties. The results indicate that adding Mn and Cr changes the morphology of Fe-rich phases. It transforms from the needle-shaped Al7Cu2Fe phase (without Mn and Cr) to the block-shaped Al7Cu2(Fe,Mn)/Al3(Cu,Fe,Mn) phases (with Mn addition), and then to the dendrite-shaped Al3(Cu,Fe,Mn,Cr) phase (with both Mn and Cr added). Moreover, numerous Cr-doped T′-Al20Cu2(Mn,Cr)3 dispersoids with the same hexagonal subunit structure as T-Al20Cu2Mn3 precipitated in Mn– Cr-containing alloys during the solid solution process.The addition of 0.4 wt% Mn and 0.1 wt% Cr together made the distribution of T′-Al20Cu2(Mn,Cr)3 dispersoids more uniform, increased their number density, and reduced their size. This is due to the opposite partitioning of Mn and Cr and slow diffusion rate of Cr. Consequently, the alloy with 0.4 wt% Mn and 0.1 wt% Cr added jointly shows superior mechanical properties, specifically an ultimate tensile strength of 473.0 MPa, a yield strength of 408.0 MPa, and an elongation of 7.06 %. The variety and morphology of Fe-rich phases significantly affect fracture behavior, and the cracks in dendrite-shaped phases form in multiple directions, boosting crack resistance during tensile deformation. The results provide guidelines for designing and developing Fe-tolerant Al–Cu cast alloys.